Gliotactin and Discs large form a protein complex at the tricellular junction of polarized epithelial cells in Drosophila. - Schulte, J.; Charish, K.; Que, J.; Ravn, S.; MacKinnon, C.; Auld, V.J. (Journal of Cell Science, 2006)
The tricellular junction (TCJ) forms at the convergence of pleated septate junctions (SJs) from three adjacent cells in polarized epithelia and is necessary for maintaining the transepithelial barrier. In Drosophila, the transmembrane protein Gliotactin was the first identified marker of the TCJ, but little is known about other molecular constituents. We now show that Gliotactin associates with Discs large at the TCJ in a Ca(2+)-dependent manner. Discs large is essential for the formation of the TCJ and the localization of Gliotactin. Surprisingly, Gliotactin localization at the TCJ was independent of its PDZ-binding motif and Gliotactin did not bind directly to Discs large. Therefore Gliotactin and Discs large association is through intermediary proteins at the TCJ. Gliotactin can associate with other septate junction proteins but this was detected only when Gliotactin was overexpressed and spread throughout the septate junction domain. Gliotactin overexpression and spread also resulted in a reduction of Discs large staining but not vice versa. These results suggest that Discs large participates in different protein interactions in the SJ and the TCJ. Finally this work supports a model where Gliotactin and Dlg are components of a larger protein complex that links the converging SJs with the TCJ to create the transepithelial barrier.